Twenty-five astronomical observations that changed the world : and how to make them yourself - Marett-Crosby, Michael (The Patrick Moore Practical Astronomy Series, 2013)
Human history is also the record of our fascination with the sky, and to look upwards is to follow in the steps of such greats as Galileo and Newton. What they and others once saw in the heavens for the first time, amateur astronomers can discover anew using this guide to twenty-five of the greatest journeys through space.   Starting with our most visible companion the Moon, each chapter offers a step-by-step walk-through of famous astronomical observations from the history of science. Beginning with the easiest targets, sometimes even accessible with the naked eye, the challenges become progressively more difficult. Beginner astronomers and more experienced hobbyists alike can reacquaint themselves with the wonders of our fellow planets and even reach far beyond our own solar system to touch on such incredible phenomena as the birth of new stars in nebula systems and the deceptive nothingness of black holes. The would-be astronaut can spy the International Space Station in orbit with binoculars or the doomsday prophet can search for new comets. Along the way, easily digestible mini-lessons inform the reader on the initial discovery of then-new celestial bodies and subsequent advances in our understanding of the cosmos.   Relying only on binoculars or small astronomical telescopes for most of the observations, and including background on the science of each phenomenon, this exploration of the skies is easy to follow and packed with useful information and fun tidbits. These practical observations put us in contact with all the history and culture surrounding them: through scientific speculation and literature to those first fuzzy images made in 1959 by the Russian space probe Luna 3.